The Correlation Between Students’ Reading Habits And Essay Writing Ability In EFL - Abdul Syahid; Muhammad Noor Fauzan; Muliana Setia Hapsari; Siti Nurrahmah; Syahrul Mubaroq; Tiara Nur Fatimah Almadani (Jurnal Pendidikan dan Sastra Inggris, 2023)
This correlational study explains the relationship between reading habits and essay writing abilities in 3rd semester students in the Essay Writing course. This research, which was conducted at a state Islamic religious institution in Indonesia, used a purposive sampling technique for English Language Education students using a quantitative approach using tests and evaluations based on essay rubrics from the international reading association NCTE for data collection. The normality test shows a non-normal distribution of the reading and writing variables. Shows a weak negative correlation between reading habits and essay writing ability. This discussion emphasizes the importance of understanding the different relationships between these variables, challenging common beliefs and encouraging further exploration in this area. These findings contribute to existing knowledge, indicating that in this study, reading habits did not have a significant effect on essay writing ability.